Funding arts and culture: Everyday experiences and organisational portfolio precarity. (June 2023) - Ashton, Daniel
This article examines the everyday experiences of arts and cultural organisations in negotiating the UK government and cultural policy priority for funding income diversification. Identifying the challenges of declining public funding and the connected pressures for arts and cultural organisations to be accountable, this article positions income diversification in relation to New Public Managerialism. In doing so, the need to examine the everyday experiences of how arts and cultural organisations engage with and respond to the income diversification priority is established. This article then presents findings from empirical research with arts and cultural organisations under the following three themes: balancing simultaneous sources, managing timelines and working through change. The discussion develops this analysis by identifying portfolio working and precarity as prominent and significant features of organisations' experiences. Portfolio working is evident in how organisations identify and manage multiple, potential funding sources. Precarity is evident in the uncertainty and instability of managing the multiple funding sources, and in the way that organisations address operational issues of planning and working practices. To conclude, the concept of organisational portfolio precarity is proposed as a way to critically understand the everyday situations and implications of how art and cultural organisations respond to the income diversification priority.